DEVELOPMENT OF STUDENTS’ WORKSHEETS BASED ON GUIDED INQUIRY MODELS TO TRAIN SCIENCE PROCESS SKILLS AND CRITICAL THINKING SKILLS IN PROJECTILE MOTION - Suzan Nathania Salim; Jane Koswojo (Magister Scientiae, 2020)
In facing AEC (ASEAN Economic Community) which has impacted education, the young generation of a nation must have higher-order thinking skills. One of the ways to achieve that purpose is through practicing science process and critical thinking skills since they start education early. To exercise those skills in our students, we need to develop supporting learning materials. In this study, we develop learning materials on the topics of projectile motion based on Guided Inquiry Model through developmental research within ADDIE. The learning materials are validated by two validators before tested to 19 students of X MIPA 2 at St. Hendrikus Senior High School. The results of the validation process indicate that the developed lesson plan is, the developed student’s worksheet, and evaluation/assessment plan are very valid with score of 3.76, 3.67, and 3.61 (out of 4) , respectively. The field test indicates that the lesson plan is implemented quite well. According to the pre- and posttest results, students’ critical thinking skills improve, which is indicated by average N-gain score of 0.39. Descriptively it also can be observed that the students’ science process skills develop throughout the implementation process. Besides, according to the questioner answers, students give positive responses to the learning materials and their implementation. In conclusion, the evaluation shows that the students achieve good critical thinking and science process skills. The developed learning materials support learning activities which involve practicing in critical thinking skills and science process skills.